Life cycle of Eimeria krijgsmanni-like coccidium in the mouse (Mus musculus) - Matsui, T.(Kyorin Univ., Mitaka, Tokyo (Japan). School of Medicine); Fujino, T; Kobayashi, F; Morita, T; Imai, S (Journal of Veterinary Medical Science, 2006)
Life cycle of Eimeria krijgsmanni-like coccidium isolated from the feces of naturally infected mice purchased from commercial sources was examined. The parasite was purified by single oocyst isolation and maintained by passage in the mice before experiments. The sporulated oocysts were ovoid or ellipsoid, measuring 19.3x14.8 microm on average. One or two small polar granules were present. Micropyle and oocyst residuum were absent. Sporocysts were ellipsoid, measuring 11.6x7.2 microm on average with a small Stieda body and sporocyst residuum. Six groups of respective 5 mice (4-week-old) were inoculated with doses varying from 2.0x10E1 to 10E6 oocysts. All the mice examined began to shed oocysts from 7 day postinoculation (PI) and their maximum number of oocysts per gram of feces were 10E6 on day 8 PI. Patency was 6 or 7 days. This parasite had severe virulence to the mice that is, the mice given 10E6 oocysts showed anorexia, diarrhoea and rough hair from 1 day and all of them died on day 3 PI. The mice given 10E3 or more oocysts showed the clinical signs described above from day 5 and 4 of them received 10E5 died on day 9 or 10 PI. The parasites occurred within the epithelial cells of cecum, colon and rectum of infected mice. Sporozoites, 13.9x3.0 microm, with two large refractil bodies on side of the nucleus located subcentrally were observed on day 1 and 2 PI. Merozoites were first observed at 24 hr PI, and sexual stages were found from 4 day PI. No parasites were detected in the small intestine and mecenteric lymph nodes.